Assessment of the Fish Market Structure along the North Tamil Nadu Coast - Shyam. S. Salim; Monolisha S; Narayana Kumar R; Geetha R (Journal of Indian Fisheries Association, 2020)
The paper attempts to analyse the market structure of the selected marine fish markets of the Tamil Nadu Coast. It deals with understanding the market structure and its market potential. The major developments of the market strengthening, trade and the market flow were discussed. The market structure analysis of the selected markets indicates that the trade flow is widely distributed covering the diﬀerent parts of the state and other consumption destinations. Lack of appropriate infrastructure, adequate amenities and low product diversity act as limiting factors in fish trade in majority of the markets studied. While addressing the economics and the market structure, the limitations involved in market developments were also taken into account and registered during the study. The study suggests the need for improved sanitation, hygienic conditions for clean water and waste disposals stands as a common constraint experienced by the marketers of the Tamil Nadu coast.